Идеологические ориентиры стран Евразийского союза (Եվրասիական միության երկրների գաղափարախոսական ուղենիշները) - Ենգոյան Աշոտ (YSU Journal of International Affairs, 2014)
In Russian social life the idea of activating the conservative approaches towards the social processes is being strengthened. The conservative ideological system, which is becoming dominant in Russia, is definitely close to the post-Soviet societies and, in the future, it will be estimated as a dominant system in Eurasian Union as well. However, contrary to the main argument of the Eurasian integration, it is pushing forward not the economic but the spiritual-moral aspects of social development which have always beensignificantly different among the people who live in post-Soviet area. Therefore, there can appear some difficulties in the ideological field of already new union. The conservative liberalism could be considered as the most acceptable ideological system for the post-Soviet societies which, first and foremost, has a liberal orientation. At the same time it underlines the significance of moral norms, the social progress observes as a necessary process of human community development, but without shocks and excesses.